Yayasan UMP introduces Publication Incentive Scheme for postgraduate students - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 28 January 2022 - Yayasan UMP introduced the Publication Incentive Scheme as an incentive for postgraduate students at Universiti Malaysia Pahang (UMP) to produce high quality research articles and make the university an international reputation.